2001
DOI: 10.1177/00238309010440020501
|View full text |Cite
|
Sign up to set email alerts
|

A Direct Assessment of the Relation Between Shared Knowledge and Communication in a Referential Communication Task

Abstract: The present paper introduces a way to document quantitatively the changing relation between shared knowledge and communication over time. It is often assumed that people engaged in prolonged interaction come to share more knowledge over the course of interaction, and, further, it is assumed that this increase in shared knowledge enables them to communicate more efficiently with each other. In Experiments 1 and 2, this assumption was evaluated by monitoring the participants' knowledge of the experimental stimul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…To distinguish between potential encoding and retrieval explanations for older adults' difficulties with audience design, we identified a subset of 8 older adults who, during the familiarization phase, showed the strongest tendency to shorten their descriptions from Rounds 1 and 2 to Rounds 5 and 6 ( M = 31.9% decline in the number of words per description) and whose descriptions showed the most evidence of incorporation ( M = 56.8%). In general, the more that individual speakers refine their descriptions during the card-matching task, the more likely it is they are encoding partner-relevant information (Clark & Wilkes-Gibbs, 1986; Nohara-LeClair, 2001). Therefore, we then examined the extent to which these 8 speakers showed evidence for audience design during the picture-description task.…”
Section: Discussionmentioning
confidence: 99%
“…To distinguish between potential encoding and retrieval explanations for older adults' difficulties with audience design, we identified a subset of 8 older adults who, during the familiarization phase, showed the strongest tendency to shorten their descriptions from Rounds 1 and 2 to Rounds 5 and 6 ( M = 31.9% decline in the number of words per description) and whose descriptions showed the most evidence of incorporation ( M = 56.8%). In general, the more that individual speakers refine their descriptions during the card-matching task, the more likely it is they are encoding partner-relevant information (Clark & Wilkes-Gibbs, 1986; Nohara-LeClair, 2001). Therefore, we then examined the extent to which these 8 speakers showed evidence for audience design during the picture-description task.…”
Section: Discussionmentioning
confidence: 99%
“…The emergence of shared meaning is hypothesized to precede learning and action in groups [66]. Its purpose is to provide the foundation for mutual understanding that will facilitate coordination [96] and communication [97]. A shared meaning clarifies why the team is needed, what it should do, who should be involved, etc.…”
Section: The Functions Of Team Mental Modelsmentioning
confidence: 99%
“…For example, Rentsch and Klimoski [104] suggested that normative variables, such as trust and cooperation, play a significant role in the formation of shared mental models. Several authors argued for the importance of communication processes in fostering TMM (e.g., [97]; [95]; [78]; [53]). These authors view overt communication in teams, and participants' awareness of the shared knowledge, as important factors in team performance.…”
Section: Process Factorsmentioning
confidence: 99%